A randomised, parallel-group clinical trial comparing bedinvetmab to meloxicam for the management of canine osteoarthritis - Innes, John F.; Lascelles, B. Duncan X.; Bell, Daniel; Tulloch, Robert; McVey, Alex; Northcott, Chad; Welbourn, Mahala; Higgins, Kate; Horakova, Veronika; Maddox, Thomas W. (Frontiers in Veterinary Science, 2025)
Bedinvetmab (Librela®), a fully canine anti-nerve growth factor monoclonal antibody, was compared to the non-steroidal anti-inflammatory drug (NSAID) meloxicam in dogs for the management of osteoarthritis-related pain in a randomised, open-label, multicentre, parallel-group study. Subjects were recruited from general practices as client-owned dogs with appendicular osteoarthritis. Dogs were block randomised 1:1 to either daily oral meloxicam or bedinvetmab, administered subcutaneously once a month. The primary endpoint for efficacy was the change from baseline in the Canine Orthopaedic Index (COI) score. Linear mixed-effects models were used for statistical analysis conducted on a per-protocol and intent-to-treat basis. We hypothesised that bedinvetmab would demonstrate superior efficacy and safety compared to meloxicam; the number needed to harm (NNH) for meloxicam, relative to bedinvetmab, was calculated. Of the 190 screened dogs, 101 were randomised (bedinvetmab 52; meloxicam 49). Overall, both treatment groups showed a significant reduction in COI scores relative to baseline (p < 0.001). The bedinvetmab group experienced a larger mean reduction in COI scores, but this was not statistically significant. A significant effect of the visit was observed, with later visits showing a significantly greater reduction in COI compared to Visit 2 (p < 0.001). The bedinvetmab group reported four (AEs), whilst the meloxicam group reported 17, with nine of those being gastrointestinal system disorders. Additionally, more dogs in the bedinvetmab group completed the study (n = 44) compared to those in the meloxicam group (n = 33). This is the first study to compare bedinvetmab to an NSAID for the management of osteoarthritis-related pain in dogs. The results suggest that both products are equally effective in managing OA pain, with efficacy improving over time for both treatments. Bedinvetmab was associated with fewer AEs. These data will aid clinicians and pet owners in choosing analgesic options for dogs with osteoarthritis.